Relevant Problems of Legal Regulation of IT Modernization of Local Self-Government Technologies in Russia - SOLOVEV, Sergey Gennadevich; KIREEV, Valeriy Vitalievich; SOTNIKOVA, Liliya Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).29, 2019)
The research is devoted to understanding the problematic issues of the regulation of the IT modernization of traditional local self-government technologies in Russia. The key theoretical and practical problems related to the content and procedural aspects of the regulation of the introduction of e-democracy forms at the municipal level have been considered. A set of legal measures aimed at improving the content of the analyzed legal structures has been proposed.